Scaffolding Based on Telolet Game in Teaching Integers - Yunita Oktavia Wulandari; Nia Wahyu Damayanti (Malikussaleh Journal of Mathematics Learning (MJML), 2018)
Scaffolding is defined as help that can assist students to solve problems or understand concepts that were not able to complete independently. In modern times, the concept of technology-based Scaffolding in learning has developed. In this study an educational game called "Telolet" was designed with the aim of providing Scaffolding to students who experienced difficulties in integers. The problems in this study consist of closed problems, opened problems  and some problems are related to integers. The purpose of this study is to provide students with a whole understanding in integers so that they can educate students with the right concepts. The results of this study, Scaffolding based on the game "Telolet" can help students who have difficulty in integer problems. Students excited to solve problems in this game because they felt challenged.